A Phase Loss Fault Diagnosis Strategy for EV Motor Control System - YANG Linlin; CHEN Lei; CHEN Jianming; LIU Wang (Kongzhi Yu Xinxi Jishu)
In order to improve the accuracy of fault diagnosis for EV motor control system under different current conditions, this paper proposed a fault diagnosis strategy of phase loss based on the multi-variable condition, which is derived from Matlab simulation analysis of an EV motor control system. Software implementation process of the diagnosis strategy was given, and HIL fault injection test was conducted through dSPACE real-time system at last. The test results show that the strategy can accurately diagnose phase loss fault of three-phase power line under special operating conditions such as start-up, operation and current sensor fault, and effectively improve the reliability and safety of vehicle driving.